The Diagnosis and Treatment of Early Pregnancy in Caesarean Scar (CSP) - a Clinical Description of the Case - Gruszka, Jakub; Świercz, Grzegorz; Zwierzyńska, Anna; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2022)
Early pregnancy, in the lower part of the uterus, in the Caesarean scar (CSP), is a type of ectopic pregnancy. It can cause serious complications if left untreated. CSP, with a positive embryo/foetal heart function, treated on a waiting list, has been associated with a high, maternal burden, haemorrhaging, early uterine rupture, hysterectomy and severe AIP. Some pregnancies, made the more complicated with CSP, can progress to term, making it difficult to decide whether termination of the pregnancy may be the only treatment option for these women. Expectant management in CSP, without cardiac activity, may be an option because of the low risk of maternal complications requiring immediate intervention. Nevertheless, close monitoring is recommended, in order to avoid complications in pregnant women. Endovaginal USG is the main method in the diagnosis of this disease, since it is not affected by external factors. Therefore, this type of ultrasound diagnosis has better diagnostic efficacy, in the case of this type of ectopic pregnancy CSP.